Formulation and development of Serratiopeptidase enteric coated tablets and analytical method validation by UV Spectroscopy - Vijay Kumar Panthi; Saurav Kumar Jha; Raghvendra Chaubey; Rudra Pangeni (International Journal of Analytical Chemistry)
Serratiopeptidase (SRP) is a proteolytic enzyme that emerged as one of the most potent anti-inflammatory and analgesic drugs. The purpose of the present study was to formulate and evaluate enteric-coated tablets for SRP and investigate their stability using a simple and validated analytical method by ultraviolet (UV) spectroscopy. The colloidal silicon dioxide (2.50%), sodium starch glycolate (3.44%), and crospovidone (2.50%) were used as appropriate excipients for the development of core part of tablets. To protect the prepared tablets from acidic environment in the stomach, white shellac, castor oil, HPMC phthalate 40, and ethyl cellulose were used. The seal coating and enteric coating attained were 2.75% and 6.74%, respectively. SRP was found to be linear at 265 nm in the concentration range of 25–150 µg/mL. The results revealed that our developed method was linear (R2 = 0.999), precise (RSD % = 0.133), and accurate (% recovery = 99.96–103.34). The formulated SRP tablets were found to be stable under accelerated conditions as well as under room temperature for 6 months (assay %: >97.5%). The in vitro drug release study demonstrated that enteric-coated tablets were able to restrict SRP release in both acidic environments: 0.1 N HCl and simulated gastric fluid (pH 1.2). Moreover, at 60 minutes, the formulated SRP tablets revealed 13.0% and 8.98% higher drug release in phosphate buffer (pH 6.8) and simulated intestinal fluid (pH 6.8), respectively, compared to the marketed tablet formulation. This study concludes that enteric-coated tablets of SRP with higher drug release in the intestine can be prepared and examined for their stability using validated analytical technique of UV spectroscopy.